PENGARUH LITERASI KEUANGAN, RISIKO, MOTIVASI, OVERCONFIDENCE, HERDING DAN LOSS AVERSION TERHADAP KEPUTUSAN INVESTASI (Studi Kasus pada Karyawan PT Kanindo Makmur Jaya 1) - PUTRI SARI, NADYA; ADI WIBOWO, PURWO (AkMen JURNAL ILMIAH, 2025)
The purpose of this study was to determine the effect of financial literacy, risk perception, investment motivation, overconfidence, herding behavior and loss aversion on investment decisions among employees of PT Kanindo Makmur Jaya 1 with a population of 6.330 employees. In this study, data was collected by distributing questionnaires and using purposive sampling techniques to obtain a sample of 104 employees. The data analysis method used is multiple linear regression analysis and uses the SPSS application so that the research results show that financial literacy, investment motivation, risk perception, loss aversion and herding behavior do not influence investment decisions. Meanwhile, overconfidence has a positive and significant effect on investment decisions.